2015
DOI: 10.1007/s13277-015-3596-7
|View full text |Cite
|
Sign up to set email alerts
|

miR-125/Pokemon auto-circuit contributes to the progression of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a type of human malignant tumor occurring in hepatic tissues with high mortality. Patients benefit little from current therapeutic modalities, at least partially due to the lack of complete elucidation of molecular network regulating HCC. miR-125 and Pokemon are well-recognized tumor suppressor and oncogenes for HCC, respectively. However, the underlying mechanism by which the two genes exert their functions and the relationship between miR-125 and Pokemon is still unexplored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Few miRNAs have been shown to play an oncosuppressive role in HCC 39 , 40 . Among them, miR-125a inhibits cell proliferation, angiogenesis and cell migration by downregulating the expression of sirtuin-7 34 , vascular endothelial growth factor A, matrix metalloproteinase-11 35 , Zbtb7a 41 , and c-RAF 42 . Targeting of Bcl2 and caspase 3 may also be relevant for the antiangiogenic activity 43 of the miRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Few miRNAs have been shown to play an oncosuppressive role in HCC 39 , 40 . Among them, miR-125a inhibits cell proliferation, angiogenesis and cell migration by downregulating the expression of sirtuin-7 34 , vascular endothelial growth factor A, matrix metalloproteinase-11 35 , Zbtb7a 41 , and c-RAF 42 . Targeting of Bcl2 and caspase 3 may also be relevant for the antiangiogenic activity 43 of the miRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding is consistent with the report by Chen et al [ 22 ] that cancer cells harboring Dicer1 hotspot mutants that had lost 5p miRNA biogenesis, showed increased proliferation rate and upregulated expression of cell cycle promoting genes compared to cancer cells with wild-type Dicer1 , suggesting the tumor-suppressing effect of Dicer1 in wild-type cells. Similar to the Dicer1 hotspot mutant cells, the Dicer-Pten DKO mouse tumor cells showed significant reduced expression of miRNAs such as let-7 and miR-125 (Figure 3B ), which have been shown to harbor tumor suppressor functions [ 22 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocellular carcinoma (HCC) it has been shown that the ectopic expression of miR-125a inhibits proliferation and metastasis by targeting MMP11 and VEGF [133], while others showed that ectopic expression of miR-125b reduces the cellular proliferation and cell cycle progression of HCC cells by targeting Mcl-1 and IL6R [134]. In another study the authors showed that miR-125b suppresses human liver cancer cell proliferation and metastasis by directly targeting oncogene LIN28B2 [135]. Additional miR-125 interactors in HCC had been identified in the years, including Pokemon [136], TRAF6 [137], hexokinase II [138] and FOXM1 [139].…”
Section: Mir-125 and Cancermentioning
confidence: 99%